Inferior Vena Cava Filters and Prevention of Recurrent Pulmonary Embolism - Malhotra, Anuj; Kishore, Sirish; Trost, David; Madoff, David C.; Winokur, Ronald S. (Seminars in Interventional Radiology, 2018)
Although inferior vena cava (IVC) filters have a clear role in preventing recurrent pulmonary embolism (PE) in patients with venous thromboembolism who cannot be anticoagulated, the role of filters in patients who are candidates for anticoagulation is controversial. With limited and conflicting data, practitioners often have to make an educated patient-specific decision when encountering this scenario. This article reviews the available data on the efficacy and risks associated with adjunctive IVC filter use to prevent recurrent PE.
Keywords: venous thromboembolism; deep vein thrombosis; pulmonary embolism; inferior vena cava filters; interventional radiology